2002
DOI: 10.3201/eid0802.010165
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Unexplained Deaths and Critical Illnesses Due to Possibly Infectious Causes, United States, 1995-1998

Abstract: Population-based surveillance for unexplained death and critical illness possibly due to infectious causes (UNEX) was conducted in four U.S. Emerging Infections Program sites (population 7.7 million) from May 1, 1995, to December 31, 1998, to define the incidence, epidemiologic features, and etiology of this syndrome. A case was defined as death or critical illness in a hospitalized, previously healthy person, 1 to 49 years of age, with infection hallmarks but no cause identified after routine testing. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…As in this study, where the majority (7/22) of USII cases had respiratory illness, surveillance from Taiwan also found that respiratory syndromes were most common, accounting for 59% of cases [17]. Respiratory syndromes were also the second most common presentation for the US system, accounting for 26% of cases, although this was closely preceded by neurological presentations (29%) [18]. The latter were less common among our cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As in this study, where the majority (7/22) of USII cases had respiratory illness, surveillance from Taiwan also found that respiratory syndromes were most common, accounting for 59% of cases [17]. Respiratory syndromes were also the second most common presentation for the US system, accounting for 26% of cases, although this was closely preceded by neurological presentations (29%) [18]. The latter were less common among our cases.…”
Section: Discussionsupporting
confidence: 71%
“…To our knowledge, there have been only two similar surveillance systems [17,18] described previously in the literature although these were not specifically developed for mass gatherings.…”
Section: Discussionmentioning
confidence: 99%
“…Our annual rate is comparable to that reported in the literature from similar surveillance systems in the United States and Taiwan, despite methodological differences such as the inclusion and exclusion criteria and the extent of laboratory investigations. In Taiwan, 0.12 cases per 100,000 population were reported in 2000-05 [8] and in the United States, 0.5 cases per 100,000 population (range: 0.3-2.3 per 100,000 population) were reported during 1995-98 [4]. The majority of USII cases in our pilot study were reported in the first three months of surveillance.…”
Section: Discussionmentioning
confidence: 53%
“…Examples, including the international spread of severe acute respiratory syndrome (SARS) and the influenza A(H1N1)pdm09 pandemic, illustrate that new and emerging infections can spread through major transport hubs in a matter of days [2,3]. Such new and emerging diseases can pose difficulties in diagnosis and may present as undiagnosed serious infectious illness (USII) [4]. These could be missed by traditional surveillance, necessitating the development of new infectious disease surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation